ANALISIS KEUNTUNGAN INDUSTRI SUSU KEDELAI UD. TIGA BERSAUDARA DI KELURAHAN TAAS KECAMATAN TIKALA BARU - Cyntia Rumambi; Lyndon R.J. Pangemanan; Yolanda P.I. Rori; Melissa I.G. Tarore (Universitas Sam Ratulangi, 2013)
ABSTRACTThe objective of this study is to examine how much profit received soybean milk industry profitability analysis of UD. Tiga Bersaudara Taas Tikala Baru for one time production process.Research methods used in this research is a case study on the UD. Tiga Bersaudara Taas Tikala Baru. Data taken in the form of primary data obtained by using the interview technique directly to the owner of the business interview soy milk on UD. Tiga Bersaudara Taas Tikala Baru. The interview is using a list of questions that have been prepared.The result of research was soybean milk industry UD. Tiga Bersaudara has been sold at supermarket Fresh Mart and Karombasan market. Marketed in supermarkets and on the market fresh mart and karombasan market. Average number of requests in each place different, Karombasan market could be sold. 50 packs/day. While in the supermarket fresh mart could be sold 37 bottles/day. Fresh mart supermarket then divide there 37 bottles of soybean milk to every branch of fresh Mart in the city of Manado.UD. Tiga Bersaudara on the research at soybean milk UD. Tiga Bersaudara at Kelurahan Taas Kecamatan Tikala Baru,it could be concluded that the amount of output produced for one-time production process 43.460 ml devided in 37 ml bottles (21.460 ml) marketed in the fresh mart and 50 plastic was (22.000 ml) were sold in the market karombasan. For a one production process of soybean milk, the profit was Rp. 125.691,5.- was the the business beneficial because r/c ratio > 1 is equal to 1,48. Advice can be given to the advancement of this industry is the need for keeping the soybean milk industry in detail again and the need for of working capital loans to increase production so that profits will increase.